DECISION SUPPORT SYSTEM FOR OIL PALM SEED SELECTION USING THE SIMPLE ADDITIVE WEIGHTING METHOD - Situngkir, Silvia Wulandari (Media Jurnal Informatika, 2025)
Oil palm is one of the most important plantation commodities in Indonesia's plantation development. According to the Indonesian Ministry of Agriculture (2014), the total area of oil palm plantations in Indonesia is 11 million hectares, double the area in 2000. Indonesia is one of the largest palm oil producers in the world, providing employment for 16 million people, both directly and indirectly. The use of superior seeds is one of the important factors that determine the growth of oil palm. Maximum production can be achieved if the plants come from good quality seeds. Decision Support System is an interactive system that supports decisions in the decision-making process through alternatives obtained from the results of data processing, information and model design. By utilizing data processing technology that can provide solutions for farmers in choosing good seeds. In this research, the Decision Support System was developed with the Simple Additive Weighting Method where this system will assist farmers in determining quality seedlings ready for planting based on the criteria of the number of leaves, the age of the seedling in months, the height of the seedling in centimeters, and the diameter of the stem. With the results of the type of seedling DxP PPKS 718 3 is the most superior type of seedling for planting with a preference value obtained of 100, while the type of palm seedling DxP PPKS 239 1 is the worst quality seedling among 24 alternatives with a total preference of 24.